Serum progranulin as a predictive marker for high activity of antineutrophil cytoplasmic antibody‐associated vasculitis. Issue 11 (9th October 2021) - Yoon, Taejun; Lee, Lucy Eunju; Ahn, Sung Soo; Pyo, Jung Yoon; Song, Jason Jungsik; Park, Yong‐Beom; Lee, Sang‐Won
Abstract: Background: This study investigated whether serum progranulin could act as a predictive marker for high disease activity of antineutrophil cytoplasmic antibody (ANCA)‐associated vasculitis (AAV). Methods: Fifty‐eight AAV patients were included in this study. Clinical and laboratory data were obtained at blood collection. The Short‐Form 36‐Item Health Survey Physical and Mental Component Summaries (SF‐36 PCS and SF‐36 MCS), Birmingham Vasculitis activity score (BVAS), Five‐Factor Score (FFS), and Vasculitis Damage Index (VDI) were assessed as AAV‐specific indices. Whole blood was collected and serum samples were isolated and stored at −80°C. Serum progranulin concentration was quantified by ELISA kits. Results: The median age of patients was 63.0 years (19 men). The median BVAS was 11.0, and the median serum progranulin level was 49.0 ng/ml. Serum progranulin was significantly correlated with BVAS, FFS, erythrocyte sedimentation rate, C‐reactive protein level, SF‐36 PCS, haemoglobin, and serum albumin. Severe AAV was arbitrarily defined as the highest tertile of BVAS (BVAS ≥16). When the cut‐offs of serum progranulin were set as 55.16 ng/ml and 43.01 ng/ml for severe AAV, AAV patients with serum progranulin ≥55.16 and 43.01 ng/ml had significantly higher risks of severe AAV than those without (relative risk (RR) 4.167 and 4.524, respectively). Conclusions: Progranulin might play an anti‐inflammatory role in AAV pathogenesis and serum progranulin could be used as a predictive marker for high activity of AAV. Abstract : Serum progranulin was significantly correlated with BVAS ( r  = 0.342) as well as acute‐phase reactants such as ESR ( r  = 0.379) in AAV patients. AAV, antineutrophil cytoplasmic antibody‐associated vasculitis; BVAS, Birmingham vasculitis activity score; CRP, C‐reactive protein; ESR, erythrocyte sedimentation rate.